Structure of the Malaysian economy: an input-output analysis - Saari, Mohd Yusof (Khazanah Research Institute, 2018)
This report aims to give readers an empirical view of the supply side of the Malaysian economy, using an input-output (IO) table approach. The IO table dataset was obtained from the Department of Statistics Malaysia (DOSM) and is published every five years. The table provides comprehensive data on not only the contribution of each sector (using the Malaysia Standard Industrial Classification (MSIC)), but also the interlinkages between sectors. This report discusses four areas that are pertinent to the assessment of the economy’s structure: i) re-evaluation of the contribution of international trade to the economy; ii) detecting interlinkages between sectors of the economy; iii) analysing domestic and foreign value-added in free zones in greater detail; and iv) evaluation of the role of small and medium enterprises (SMEs). For an empirical assessment, the standard IO table is extended to capture the four areas of analysis. A common theme throughout the chapters of the report is that it aims to depart from conventional methodologies and emphasises sectors that have potential to contribute greater domestic value-added for Malaysia. Hence, the report also gives insights for policymakers to consider when formulating industrial policies.